JENIS POHON PENGHASIL BUAH-BUAHAN KONSUMSI DI TEMBAWANG DUSUN TIGA DESA DESA TIRTA KENCANA KECAMATAN BENGKAYANG KABUPATEN BENGKAYANG - Siringo, B.W Eko; Fernando, Togar; Muflihati, . (JURNAL HUTAN LESTARI, 2017)
Tembawang forest is a former long house area that is overgrown by various types of fruit tree. The plants producing fruits forest is one of very infortant natural potential for local comunity because they have many benefits for instance to consumption and other needs. The purpose of this research is to record morphological traits and to do inventory kinds of the plants producing fruits is located at Tembawang forest in Tiga Desa village. There are two methods used in this research they are survey in field and interview. According to result of two methods have been done in Tembawang forest then it found there were 16 kinds of fruits crop at 6 lanes of observation were found 33 swath, and numbers of individual 313 individuals. Index shows that there are two kinds of the plants producing fruits and many found in Tembawang forest they are durian (Durio kutejensis Hassk. Becc) of the family Malvaceae and rubber tree (Hevea brasiliensis Muell.Arg) from the family Euphorbiaceae.Â Keywords : Forest Tembawang, Producing fruits, Tirta Kencana Village.